Altitudinal and household breeding patterns of the medically important mosquitoes Aedes aegypti, Aedes albopictus and Culex quinquefasciatus in Nepal - Sunita Baral; Pramod Joshi; Bishnu P. Marasini; Ishan Gautam; Meghnath Dhimal; Ruth Muller (PLoS ONE, 2026)
Medically relevant mosquitoes have established populations across Nepal, adapting to diverse environmental conditions and altitudes. In addition to arbovirus vectors, the presence of Culex quinquefasciatus , a primary vector of lymphatic filariasis, underscores the need for comprehensive mosquito surveillance. This study investigated the presence, abundance, container preferences, and altitudinal distribution of Aedes aegypti , Aedes albopictus , and Cx. quinquefasciatus across selected districts in Nepal. We also examined the co-occurrence of Aedes species and their association with container type and location. An entomological survey was conducted along an altitudinal transect from 140 meters above sea level (m asl) (Chitwan) to 2340 m asl (Dolakha). Immatures were collected from 1,157 water-holding containers across 636 households using dipper and dropper techniques, while adults were captured using BG-Sentinel traps. Immatures were reared to adulthood for identification, while non-reared specimens were identified via microscopic slides. A total of 1,323 immature and 158 adult mosquitoes were recorded. Among immatures, Ae. albopictus (47.6%) was the most abundant, followed by Ae. aegypti (43.4%). Adults were predominantly Cx. quinquefasciatus (82.9%). Plastic bottles and drums were the most common larval habitats. Aedes species were found across the study transect, from 140 to 2066 m asl. The altitude did not have a statistically significant effect on the number of collected mosquitoes ( p = 0.563). These findings highlight the widespread presence of Aedes and Culex species across different altitudes and breeding habitats. The predominance and co-occurrence of dengue vectors and Cx. quinquefasciatus in nearby households underscore the need for integrated vector surveillance and control strategies in Nepal.